1999
DOI: 10.1117/12.360157
|View full text |Cite
|
Sign up to set email alerts
|

XMM flight model mirror effective area measurements

Abstract: The high throughput X-ray Spectroscopy Mission XMM is a "Cornerstone" project of the ESA Horizon 2000 Science Programme. The optical heart of this satellite consists in 3 Mirror Assemblies (MA). Each MA includes a Mirror Module (MM) containing 58 X-ray optical quality Mirror Shells (MS) and an X-ray baffle (XRB) which reduces straylight. Two of the three MAs are equipped with a Reflection Grating Assembly (RGA) for spectral analysis. Tests are performed in the CSL FOCALX facility. The goal of the presented tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…However, when the current density further increased to 6 and 9mA/cm 2 , H-P relation couldn't explain the change of the yield strength. It has been reported that GB played an important role in the strength [17]. So the effect of the GB on the strength was investigated in the following section.…”
Section: Effect Of the Current Density On The Grain Size Of Cu-tsvsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when the current density further increased to 6 and 9mA/cm 2 , H-P relation couldn't explain the change of the yield strength. It has been reported that GB played an important role in the strength [17]. So the effect of the GB on the strength was investigated in the following section.…”
Section: Effect Of the Current Density On The Grain Size Of Cu-tsvsmentioning
confidence: 99%
“…Where m T is a Taylor-type orientation factor [17,26], σ is the resistance to deform, namely the yield strength, τ is critical resolved shear stress on the slip surface. It can be seen that a large Taylor factor indicates high yield strength.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Typically, reflectance of the focusing mirror can be conveniently measured by directly testing the mirror [8,16,17]. However, due to the inherent curvature of the mirror and the susceptibility of thin shell structures to deformation, the reflectivity can vary even within the same layer of mirror, as the grazing incidence angles differ at different positions (about 0.2 • ).…”
Section: Extp Focusing Mirror Coating Reflectance Testmentioning
confidence: 99%
“…High-energy astrophysics realized by focusing X-ray telescopes currently ranges from about 0.2 keV to 80 keV. [1][2][3][4][5] The upper range of the energy band is reached by the Nuclear Spectroscopic Telescope Array (NuSTAR). The High-Energy X-ray Probe (HEX-P) is a X-ray mission concept submitted to the 2020 Decadal Survey, that will extend the reach of broadband X-ray observations to 200 keV 6 .…”
Section: Introductionmentioning
confidence: 99%